2021
DOI: 10.1177/21514593211063320
|View full text |Cite
|
Sign up to set email alerts
|

State-Anxiety in Geriatric Patients Undergoing Surgical Treatment for Femoral Neck or Intertrochanteric Fractures

Abstract: Introduction Geriatric patients with hip fractures often experience unexpected falls and they may have unfamiliar and unpleasant experiences within a brief period. This study aimed to investigate the prevalence and levels of preoperative anxiety in patients undergoing surgical treatment for hip fractures, and to determine the anxiety-related characteristics experienced by patients during the period before and after surgery. Materials and methods We recruited a total of 75 geriatric patients who underwent surgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Several studies have investigated the period of greatest anxiety in patients who have undergone surgery other than arthroscopic knee surgery [ 15 , 16 ]. However, there are no studies investigating the period of greatest anxiety in patients who undergo arthroscopic knee surgery, except for 2 that reported changes in STAI scores before and after the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated the period of greatest anxiety in patients who have undergone surgery other than arthroscopic knee surgery [ 15 , 16 ]. However, there are no studies investigating the period of greatest anxiety in patients who undergo arthroscopic knee surgery, except for 2 that reported changes in STAI scores before and after the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…A total score ≥ 52 indicates clinically meaningful anxiety. Perioperative anxiety related to arthroscopic meniscectomy was evaluated using a questionnaire introduced in previous studies [ 15 , 16 ]. The questionnaire was divided into four areas: main cause of anxiety; most anxious moment during the entire process; most helpful factors for overcoming preoperative anxiety; and reducing postoperative anxiety.…”
Section: Methodsmentioning
confidence: 99%
“…33 The STAI questionnaire has long been used in clinical studies, particularly in orthopaedic surgery. 12,18,19 Inclusion criteria were as follows: patients must have at least 6 months of pain with appropriate medical management by orthoses and painkillers before surgery, over 18 years old, independent, and living at home, with scheduled outpatient HV surgery. Exclusion criteria were as follows: inability to understand the STAI questionnaire, refusal to participate, patients with a bilateral procedure, patient under protective measure or deprived of liberty, or missing data.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to experiencing pain and disturbed sleep, older adults with HF may also encounter a multitude of anxiety-provoking scenarios, including those involving unfamiliar or unpleasant situations, such as traveling by ambulance to reach the hospital, facing an emergency or needing surgery, and leaving the operating room under the effects of anesthesia without being adequately informed 9 . Furthermore, it has been demonstrated that POP can cause anxiety in patients who have undergone hip surgery.…”
Section: Introductionmentioning
confidence: 99%